STRATEGI TIM SUKSES MURSINI-HALIM DALAM MEMENANGKAN PILKADA TAHUN 2015 DI KECAMATAN KUANTAN MUDIK - Saputra, Andi Eko; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The regional head and deputy head of the region is directly regulated in Law No. 32 Year 2004 on Regional Government Article 56, Article 119, and Government Regulation No. 6 Year 2005 on Procedures for the Election, Legalization, Appointment and Dismissal of Regional Head and Deputy Regional Head. The elections that have taken place in Kuantan Singingi especially in the district of Kuantan Homecoming 2015 was won by the pair number 2 is a pair Mursini-Halim who had MH calls.This study aims to determine campaign strategy successful team Mursini-Halim won the election in 2015 in the district of Kuantan Mudik and to determine the factors that become supporters and obstacles in the process of political participation of the people in the election. The method used is descriptive qualitative method for collecting data from informants through interviews and explanations, the researchers can analyze a Campaign Strategy Team Success Mursini-Halim in winning elections in the District of Kuantan Mudik 2015.Keywords: Supporting Factors, Obstacles, Political Participation, Strategy.